(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This study investigates the changes in agrochemical properties of irrigated gray meadow soils, crucial for sustainable agricultural practices. Over time, anthropogenic activities and natural processes can alter soil characteristics, impacting crop productivity and environmental health. By analyzing soil samples from irrigated gray meadow areas, this research aims to assess variations in key agrochemical parameters, including pH, organic matter content, nutrient levels, and salinity. Understanding these changes is essential for implementing effective soil management strategies and mitigating adverse effects on agricultural ecosystems. The findings contribute to the development of tailored soil conservation and fertility enhancement practices, promoting the long-term sustainability of irrigated agriculture in gray meadow regions.